PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN TENAGA PENDIDIK PADA YAYASAN PERMATA MOJOKERTO - Khusnul Khotimah; Ernani Hadiyati; Jamal Abdul Nasir (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This research is aimed to: 1). Analyze the effect of motivation on commitment; 2). Analyze the effect of organizational culture on commitment; 3). Analyze the effect of motivation on teacher’s performance; 4). Analyze the effect of organizational culture on teacher’s performance; 5). Analyze the effect of motivation on teacher’s performance through commitment; 6). Analyze the effect of organizational culture on teacher’s performance through commitment. This research is a quantitative survey research using the explanatory research. The sample used is 128 respondents of all teachers at Mojokerto Permata Foundation. Each hypothesis was tested using the PLS SEM method. The results of the study prove that: 1) There is a significant positive effect of motivation on commitment; 2) There is a significant positive effect of organizational culture on commitment; 3) There is a significant effect of motivation on performance; 4) Organizational culture has a significant effect on teacher’s performance; 5) There is a significant positive effect of commitment on teacher’s performance; 6) By mediating commitment, motivation has no significant effect on the performance of teachers; 7) organizational culture has an indirect effect on the performance of teachers through commitment.